2013
DOI: 10.1177/0269216313510342
|View full text |Cite
|
Sign up to set email alerts
|

The development and piloting of the REnal specific Advanced Communication Training (REACT) programme to improve Advance Care Planning for renal patients

Abstract: There is a need to improve end-of-life care for End-Stage Kidney Disease patients, to enable them to make informed decisions about future care. Challenges include prioritising communication training among service providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 19 publications
0
61
0
Order By: Relevance
“…The other two studies did report an increase in post-intervention confidence scores; however the findings were non-significant (Bristowe et al, 2014;Krimshtein et al, 2011). These findings suggest that communication skills training does have some effect on participants' confidence; however effectiveness can be varied, and therefore we cannot conclusively argue that training will significantly improve health professionals' confidence in communicating about EoL issues with patients and families.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The other two studies did report an increase in post-intervention confidence scores; however the findings were non-significant (Bristowe et al, 2014;Krimshtein et al, 2011). These findings suggest that communication skills training does have some effect on participants' confidence; however effectiveness can be varied, and therefore we cannot conclusively argue that training will significantly improve health professionals' confidence in communicating about EoL issues with patients and families.…”
Section: Discussionmentioning
confidence: 95%
“…Seven studies were conducted in the United States of America (Betcher, 2010;Kelley et al, 2012;Kerai & Wheeler, 2013;Krimshtein et al, 2011;Schell et al, 2013;Smith et al, 2013;Zapka et al, 2006); one study in the Netherlands (Mulder et al, 2009); one study in Australia (Clayton et al, 2012); and one study in the United Kingdom (Bristowe et al, 2014). Only four studies reported sex of participants (Clayton et al, 2012;Mulder et al, 2009;Schell et al, 2013;Smith et al, 2013).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the need for ACP for dialysis patients is becoming more widely recognized (7,(24)(25)(26), and interventions to improve ACP have begun (27,28), this study begins to address the important question of how to develop and test broadly applicable strategies for implementing patient-centered ACP for all dialysis patients and their families. This study also raises questions about the role of both patient-family/friend interaction styles and patient-provider relationships in ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the very specific challenges entailed, renal-specific training may be useful, such as the training in advanced communication skills tailored to advanced kidney disease developed by Bristowe et al (25).…”
Section: Discussionmentioning
confidence: 99%